REDESIGN APLIKASI KAI ACCES MENGGUNAKAN METODE DESIGN THINKING - Ilham Ferdiansyah; Meriska Defriani; Imam Maruf Nugroho (POLITEKNIK PIKSI GANESHA, 2023)
PT Kereta Api Indonesia is a mode of transportation that presents an innovation in the form of a mobile application to support users in ordering train tickets. In this study it aims to help users of the kai access application to be more comfortable to use, and provide information about train schedules, there are problems experienced by users in using the kai access application such as there is no forward and backward seat information in premium economy class, and no ticket information sold out. In this study, the design thinking method was used as a redesign of the user interface and user experience, and usability testing as usability metrics. This study obtained the results of the Prototype redesign of the Kai Access application with an average result of SUS 82 where these results are included in grade A and can be well received by user